The Influence of Current Ratio (CR), Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) on Return on Assets (ROA) in Manufacturing Companies Listed on the IDX for the Period 2021–2023 - Ai Handayani; Dani Sopian (Dinasti Publisher, 2025)
The consistent performance of the manufacturing sector in the first quarter of 2023 has had a significant impact on Indonesia's economic development, particularly in the face of ongoing economic uncertainty. This study employs a quantitative research methodology, utilizing both descriptive and verification analyses. Its aim is to provide a comprehensive overview of company performance while examining the relationship between the Current Ratio (CR), Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) on Return on Assets (ROA). Quantitative methods are applied to a defined population or sample by collecting data using pre-established instruments and analyzing the results through statistical techniques. Descriptive analysis is used to outline the identified issues, while verification analysis assesses the validity of predetermined hypotheses. The verification analysis in this study includes classical assumption testing and hypothesis testing. A purposive sampling technique was adopted, where samples were intentionally selected based on specific criteria determined by the researchers. Out of a total population of 78 companies, only 10 were selected as samples that met these criteria. The F-table value was 2.78, and the calculated F-statistic was 76.67. Since the F-statistic exceeds the F-table value, the null hypothesis (H?) is rejected and the alternative hypothesis (H?) is accepted. This indicates that CR, TATO, DER, and NPM collectively influence Return on Assets. The coefficient of determination (R²) was 0.9842, suggesting that 98.42% of the variance in Return on Assets is explained by the independent variables CR, DER, TATO, and NPM, while the remaining 2.57% is attributed to other factors outside the scope of this study.